The motor car and its story : - Gibson, Charles R. (Service and Co. Limited, 1927)
The subject of this book was suggested by two requests made to the author. The Council of a learned Society requested him to write a paper on the History of the Moto-car; and a group of many officers, resident in India, requested him to write a book on the Science of the motor-car...